Fecal calprotectin Level in patients with IBD and noninflammatory disease of colon: a study in Babol, Northern, Iran - Majid Sharbatdaran; Amin Halakou; Mehrdad Kashifard; Ali Bijani; Alireza Firozjaei; Akram Hossaini; Sepideh Siadati (Babol University of Medical Sciences, 2018)
Background: Inflammatory bowel disease (IBD) is a chronic disease with a relapsing course of inflammation in the digestive system. Endoscopy and histopathology are the golden standard methods for detection and assessment of IBD. A distinct increase of fecal calprotectin level can be a useful marker for the diagnosis of IBD. The aim of this study was to evaluate the fecal calprotectin level in patients with IBD and without inflammatory diseases of the colon. Methods: Calprotectin levels of patients referred to the Ayatollah Rouhani Hospital of Babol, northern Iran with clinical symptoms of colon disease were evaluated. After a week, colonoscopy and biopsy were performed on all patients and they were divided into two groups. The first group included patients with confirmed IBD and the second group included patients with diseases other than IBD, patients with IBS and healthy persons. Then the measured fecal calprotectin level was compared between the two groups before colonoscopy. Results: We observed correlation between calprotection in these two groups (p<0.0001). 38 (86.8%) patients in the case group and 5 (13.2%) patients in the control group had positive fecal calprotectin test and 12 (23.1%) patients in the case group and 40 (76.9%) patients in the control group had negative results. Basad on ROC curve, the cutoff point of calprotectin was 127.65 with 73% sensitivity and 89% specificity. The area under the curve was 0.83 with 95% confidence interval, 0.74-0.91 (p<0.0001). Conclusions: The results pointed to this fact that fecal calprotectin can be a noninvasive marker in differentiating IBD from IBS